2016
DOI: 10.1007/s12020-016-1147-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of parathyroid carcinoma and thyroid disorders: A clinical review

Abstract: Parathyroid carcinoma is a rare malignancy, which usually occurs as a sporadic disease, and less frequently in the setting of genetic syndromes. Despite the association of parathyroid and thyroid disorders being quite common, the coexistence of parathyroid carcinoma and thyroid disease is rare. We reviewed the pertinent literature. The terms "parathyroid carcinoma" and "thyroid disease, hyperthyroidism, thyrotoxicosis, hypothyroidism, thyroid nodule(s), Graves' disease, autonomously functioning thyroid nodules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Risk factors are genetic disorders, neck irradiation and often sporadic [8]. Although often seen with parathyroid and thyroid disease together, coexistence of parathyroid carcinoma and thyroid papillary ca is very rare [9]. Our case is among the rare cases in this regard.…”
Section: Discussionmentioning
confidence: 79%
“…Risk factors are genetic disorders, neck irradiation and often sporadic [8]. Although often seen with parathyroid and thyroid disease together, coexistence of parathyroid carcinoma and thyroid papillary ca is very rare [9]. Our case is among the rare cases in this regard.…”
Section: Discussionmentioning
confidence: 79%
“…e simultaneous presence of thyroid and parathyroid carcinoma is extremely rare with only 15 documented cases [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] in the last 41 years, and no correlation, up to date, has been discovered between these entities [31]. Comparison of the previous cases and ours are described in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature demonstrated that at least 23 other cases of synchronous parathyroid carcinoma and non-medullary thyroid carcinoma have been reported 3 11–17. Reported patients have been mostly women (75%) with a mean age of 52 years.…”
Section: Discussionmentioning
confidence: 99%